Pola Guru PAI dalam Implementasi Proyek Penguatan Profil Pelajar Pancasila Berbasis Kearifan Pesisir di SMP Negeri 4 Kumai - Nurjanah Assyfa Rizkia, Putri; Erlinawati, Erlinawati; Hartati, Zainap (Journal of Comprehensive Science, 2025)
This study aims to find out the pattern of PAI teachers in the implementation of the project to strengthen the Pancasila student profile based on coastal wisdom at SMP Negeri 4 Kumai, Central Kalimantan. The method used is a descriptive qualitative approach with the type of field research. The subjects of the study are Teachers, Principals, Curriculum Administrators and Students of SMP Negeri 4 Kumai who are involved in the implementation of P5 based on coastal wisdom. The results show that P5 is implemented through project-based learning, discussion and reflection, technology utilization, and collaboration with coastal communities. Students are involved in making coastal specialties such as kerbas, which teach skills while instilling Pancasila values such as mutual cooperation and creativity. Despite facing obstacles such as time and resource limitations, the program is effective in shaping the character of learners and preserving the local culture. With the right pattern, the implementation of P5 based on coastal wisdom can be a relevant and contextual learning model. In conclusion, the implementation of P5 based on coastal wisdom requires an active role of teachers as facilitators and innovators in integrating the values of Pancasila with local culture. Through exploration, discussion, and collaboration, this program instills mutual cooperation, independence, and environmental sustainability. Support from various parties is needed so that P5 is effective in shaping the character of students while preserving coastal culture.